THE ANTIBACTERIAL ACTIVITY OF FRACTIONS OF ETHYL ACETATE GARCINIA LATISSIMA MIQ. STEM BARK EXTRACTS AGAINST BACILLUS SUBTILIS AND PSEUDOMONAS AERUGINOSA - Ambarwati, NENENG SITI SILFI; Malik, Amarila; Deborah, Elfira Amalia; SM, CAKRA HAGAI ARPATI; HANIF, MA’ULFI; Elya, Berna; Hanafi, Muhammad (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Objective: This research focuses on the antibacterial activities of fractions of ethyl acetate Garcinia latissima Miq. extracts against Bacillus subtilis and Pseudomonas aeruginosa. Methods: For each bacteria, the values of the inhibitory zone diameter were determined using paper discs method, while the minimum inhibitory concentration (MIC) was determined by microdilution and antibacterial assay was determined by bioautography. Fractionation was carried out using gradient elution with silica gel column as stationary phase successively increasing the separation according to the polarity (using combination of eluents; n-hexane, ethyl acetate, and methanol). Results: To determine the diameter of the inhibitory zone for each fraction, the fractions were diluted with dimethyl sulfoxide until the concentration of each fraction was 20,000 ppm. The results showed that fraction B had no inhibitory zone against B. subtilis. The inhibitory zone diameters of fractions A, C, D, E, F, and G against B. subtilis were 7.600Â±0.000, 6.767Â±0.202, 7.950Â±0.477, 7.883Â±0.901, and 9.233Â±0.231 mm, respectively. Only Fraction G had an inhibition zone diameter of 7.200Â±0.173 mm against P. aeruginosa. The active fractions were tested by contact bioautography using silica gel (60 GF254) plate and hexane:chloroform (2:3) as mobile phase for Fractions A, C, D, E, and F and chloroform:ethyl acetate (4:1) as mobile phase for Fraction G. The thin layer chromatography plates were observed under the ultraviolet light at wavelengths of 254 and 366 nm, while the others plate (using in contact bioautography) placing on agar medium that had been inoculated with the bacteria, so the compounds could be diffuse to the medium. The active compound will appeared inhibitory zones in agar medium. The determination of the MIC values using microdilution with methylthiazol tetrazolium salt showed that fractions of the ethyl acetate extracts of G. latissima Miq. stem bark inhibited the growth of B. subtilis more actively than P. aeruginosa. The highest activity of the fractions against B. subtilis was shown by fraction G, which had a MIC value of 78.125 ppm, followed by fractions F (156.25 ppm), E (312.5 ppm), D (625 ppm), C (1250 ppm), B (2500 ppm), and A (5000 ppm). The highest activity of the fractions against P. aeruginosa was Fraction G (5000 ppm), while the MIC values of other fractions were >5000 ppm. Conclusion: Further investigations should be conducted to obtain the new antibacterial compounds in fractions of ethyl acetate extract of G. latissima Miq. stem bark that effective to inhibit the growth of B. subtilis and P. aeruginosa.